La incidencia de la aglomeración urbana en la distribución espacial de emisiones contaminantes del aire - Méndez Delgado, Alba Verónica; Lugo Alvarado, Rafael; Mendoza Tinoco, David (El Colegio de México, A.C., 2022)
The functioning of large cities demands huge amounts of material and energy resources that generate polluting waste discharged into the environment. The aim of this article is to estimate the impact of factors associated with urban agglomeration on air pollution generation in Mexico’s municipalities. First, we analyse whether the pollution presents an agglomeration pattern, and then, with a Durbin Spatial Model, the relationship between pollution and urban agglomeration is estimated. The results show that car density, the number of companies, and private consumption are the factors with the greatest weight in the generation and agglomeration of air pollution.